Geographic Information Management in Local Government - Gilfoyle, Ian (CRC Press, 2009)
As early pioneers in the use of digital geographic data, many local governments in the UK were ahead of their counterparts in central government and the private sector in the application of GIS technology. To meet current challenges, local authorities must coordinate the latest technology with effective information management strategies, human and cultural issues, and organizational structures and processes. Geographic Information Management in Local Government examines the factors that are necessary to ensure that real benefits are delivered from the improved availability of geographic information.